Contralesional Application of Transcranial Direct Current Stimulation on Functional Improvement in Ischemic Stroke Mice. Issue 7 (July 2020) - Ahn, Sung Min; Jung, Da Hee; Lee, Hong Ju; Pak, Malk Eun; Jung, Young Jin; Shin, Yong-Il; Shin, Hwa Kyoung; Choi, Byung Tae
Abstract : Background and Purpose: The therapeutic use of transcranial direct current stimulation (tDCS), an adjuvant tool for stroke, induces long-term changes in cortical excitability, for example, the secretion of activity-dependent growth factors. We assessed the proper therapeutic configuration of high-definition tDCS (HD-tDCS) in the subacute stage of ischemic stroke and its underlying expression profiling of growth factors to propose a new method for ensuring better therapeutic effects. Methods: Male C57BL/6J mice were subjected to middle cerebral artery occlusion, after which repetitive HD-tDCS (20 minutes, 55 µA/mm 2, charge density 66 000 C/m 2 ) was applied from subacute phases of their ischemic insult. Behavioral tests assessing motor and cognitive functions were used to determine suitable conditions and HD-tDCS stimulation sites. Gene expression profiling of growth factors and their secretion and activation were analyzed to shed light on the underlying mechanisms. Results: Anodal HD-tDCS application over the contralesional cortex, especially the motor cortex, was more effective than ipsilesional stimulation in attenuating motor and cognitive deficits. In the HD-tDCS application over the contralesional motor cortex, positive changes in Bmp8b, Gdf5, Il4, Pdgfa, Pgf, and Vegfb were observed in the ipsilesional site. The expression of GDF5 (growth/differentiation factor 5) and PDGFA (platelet-derived growth factor subunit A) tended to similarly increase in both ipsi- and contralesional striata. However, higher expression levels of GDF5 and PDGFA and their receptors were observed in the peri-infarct regions of the striatum after HD-tDCS, especially in PDGFA expression. A higher number of proliferating or newly formed neuronal cells was detected in ipsilesional sites such as the subventricular zone. Conclusions: Application of anodal HD-tDCS over the contralesional cortex may enhance beneficial recovery through the expression of growth factors, such as GDF5 and PDGFA, in the ipsilesional site. Therefore, this therapeutic configuration may be applied in the subacute stage of ischemic stroke to ameliorate neurological impairments. Abstract : Supplemental Digital Content is available in the text.